A theology of biblical counseling : the doctrinal foundations of counseling ministry - Lambert, Heath, 1979- (Grand Rapids, Michigan : Zondervan, 2016)
Since the beginning of the biblical counseling movement in 1970, biblical counselors have argued that counseling is a ministry of the Word, just like preaching or missions. As a ministry, counseling must be defined according to sound biblical theology rather than secular principles of psychology. For over four decades, biblical theology has been at the core of the biblical counseling movement. Leaders in biblical counseling have emphasized a commitment to teaching doctrine in their counseling courses out of the conviction that good theology leads to good counseling...and bad theology leads to bad counseling. A Theology of Biblical Counseling is a landmark new book that unpacks the core theological convictions that underlie sound counseling, and practical wisdom for counseling today. Dr. Heath Lambert shows how biblical counseling is rooted in the Scriptures while illustrating the real challenges counselors face today through true stories from the counseling room. A substantive textbook written in accessible language, it is an ideal resource for use in training biblical counselors at colleges, seminaries, and training institutes. In each chapter, doctrine comes to life in real ministry to real people, dramatically demonstrating how theology intersects with the lives of actual counselees. -- Amazon
Counseling and theology: a crucial introduction -- Biblical counseling and a theology of scripture -- Biblical counseling and a theology of common grace -- Biblical counseling and a theology of God -- Biblical counseling and a theology of Christ -- Biblical counseling and a theology of the Holy Spirit -- Biblical counseling and a theology of humanity -- Biblical counseling and a theology of sin -- Biblical counseling and a theology of suffering -- Biblical counseling and a theology of salvation -- Biblical counseling and a theology for the church -- Biblical counseling and the goal of theology -- Statement from the Association Of Certified Biblical Counselors regarding mental disorders, medicine, and counseling -- Biblical counseling, general revelation, and common grace.
Includes bibliographical references and index.
Keywords: Counseling -- Religious aspects -- Christianity; Theology